Application Bea Acquisition Of Land And Building On Regional Regulation Number 10 Of 2010 Concerning Tax In The District Of Subang - Awan Gunawan; Amin Purnawan; Dudu Wawan Setiawan (Jurnal Akta, 2019)
The purpose of this research is to know and understand the procedures for collection of the Tax on Acquisition of Land and Building in Subang district, and to know and understand the barriers and solutions in the collection of the Tax on Acquisition of Land and Building in Subang district.Based on the analysis concluded that the taxation sector is one of the important factors for increasing state revenues. The Government has conducted several reforms in taxation or tax reform one product is Act No. 20 of 2000 regarding Amendment to Act No. 21 of 1997 on Tax on Acquisition of Land and Building (BPHTB is). One of the new provisions set out in the Act is the object of a legacy set forth in Article 2 paragraph (2) letter a number 5. Object inheritance tax is no definitive explanation in the Act so that the official who is authorized to perform counting BPHTB have different interpretations in terms of treatment fully shared with collective rights or by way of a deed to each heir. As a result, the amount owed BPHTB different between treatments with each other.Keywords: Bea; Land And Buildings; Local Tax.